The Application of Wordwall-Based Digital Game-Based Learning to Improve Digital Etiquette Literacy, Learning Motivation, and Student Engagement - Ina Rahmawati; Dadang Saepuloh (Jurnal Inovasi Pendidikan Ekonomi, 2025)
This research aims to test the application of the Wordwall-based Digital Game-Based Learning (DGBL) method on digital etiquette literacy, learning motivation, and student engagement in Economics lessons at SMAN 12 Tangerang Regency. This research is quantitative research with a quasi-experimental one-group pretest-posttest design. The research sample consisted of 50 students of class XI.13 at SMAN 12 Tangerang Regency, who were selected using a saturated sampling technique. The instruments used are questionnaires and questions designed based on literacy, motivation, and student involvement indicators. Data analysis used the paired sample t-test to measure differences in results before and after treatment. The research results show that Wordwall-based DGBL does not provide a significant difference in digital etiquette literacy showing a sig and amounting to 0.637 > 0.05, because the game design is less relevant to the context of students' lives. Furthermore, the wordwall-based digital game-based learning model provides a significant difference in learning motivation showing a sig value. Equal to 0.001 < 0.05. Apart from that, the wordwall-based digital game learning model also provides a significant difference in student engagement showing a sig value of 0.000 < 0.05. Wordwall-based Digital Game-Based Learning effectively increases student motivation and engagement, but it requires the development of real simulation-based game designs to support digital etiquette literacy